ANALYSIS OF HARMONIC DISTORTION REDUCTION ON MULTILEVEL INVERTERS USING SPWM MODULATION AND PASSIVE FILTER OPTIMIZATION - Muhammad Rezeki Akbar; Aripriharta Aripriharta; Sujito Sujito (Universitas Ngeri Malang, 2024)
Solar power system is a renewable energy generator which is currently experiencing quite rapid development. One of the most important components of PLTS is the inverter. Inverter is a component that is used to convert direct voltage (DC) into alternating voltage (AC). However, in its implementation, the AC wave generated by the inverter is not yet a pure sinusoidal waveform. This is because there is harmonic distortion that exceeds the permitted standards. Based on IEEE STD 519-2014, the permitted Total Harmonic Distortion (THD) is not to exceed 5%. This study aims to analyze the reduction of harmonic distortion on Multilevel Inverters by using SPWM modulation and passive filter optimization. Harmonic distortion is reduced to not exceed the permissible standard, namely 5%. This study uses the Cascaded H-Bridges Multilevel Inverter (CHB-MLI) topology using PODPWM as the modulation technique. After that, the LCL passive filter is designed using the PSO Algorithm to optimize the parameters that make up the LCL filter. The results showed that the PSO Algorithm was able to optimize the passive LCL filter design used to reduce harmonic distortion in Multilevel Inverters. With parameter values L1, L2, and Cf each of 22.163 mH, 8.888mH, and 7.0984 μF; able to reduce the THD value to 3.06%.